2019
DOI: 10.1557/jmr.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

Size-independent strength of amorphous–HCP crystalline metallic nanolayers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Broad peaks in XRD analysis indicate distortions in the lattice parameter due to differences in the size of atoms resulting in decreased crystallinity. A broad peak could indicate an amorphous structure [ 30 ], the presence of small crystalline grains [ 31 ], or a nanolayer [ 32 ]. We therefore examined the structural changes in detail using TEM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Broad peaks in XRD analysis indicate distortions in the lattice parameter due to differences in the size of atoms resulting in decreased crystallinity. A broad peak could indicate an amorphous structure [ 30 ], the presence of small crystalline grains [ 31 ], or a nanolayer [ 32 ]. We therefore examined the structural changes in detail using TEM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group reported that the ternary CuZrTi amorphous metal has excellent elastic deformation limit and structural stability compared to the binary CuZr amorphous metal. A laminate structure in which two materials are repeatedly stacked may highlight the advantages of each material. So, the two types of layers can interact complementarily in terms of mechanical and electrical properties. …”
Section: Introductionmentioning
confidence: 99%